Genetic and morphological variation analyses of Glandirana rugosa with description of a new species (Anura, Ranidae) - Shimada, Tomohiko; Matsui, Masafumi; Ogata, Mitsuaki; Miura, Ikuo; Tange, Mai; Min, Mi-Sook; Eto, Koshiro (Zootaxa, 2022)
Glandirana rugosa is known to include several geographic groups differing in sex chromosomes, and has been proven to be paraphyletic in mitochondrial phylogeny with respect to G. susurra. By analyzing genetic and morphological variation in a large number of individuals of Glandirana, we studied their taxonomic relationships. A mitochondrial DNA phylogeny, with the G. tientaiensis as outgroup, revealed two major lineages containing respectively (1) the East group of G. rugosa, G. susurra, and the Central and Southeast-Kyushu groups of G. rugosa; and (2) G. emeljanovi, and the North and West groups of G. rugosa. In contrast, in a nuclear DNA phylogeny based on SNP data, lineages of (1) G. susurra and East group, and (2) the remaining groups of G. rugosa and G. emeljanovi, were split, indicating a distinct status of the East group among G. rugosa. In adult morphology, there were only minor differences between the East group and the remaining groups of G. rugosa, but in larvae, the East group had significantly more sparse skin glands than the others. The exact type locality of G. rugosa is most probably in western Japan, not including the range of the East group. From these results, we describe the East group as a new species, G. reliquia, distinct from the remaining groups of G. rugosa. The new species with sexually homomorphic chromosomes is thought to represent a basic stock of Japanese Glandirana, which existed far before G. rugosa originated.